Marketing Communication Analysis of the Consumer Decision Making Process - Abrina S. Wardhana; Pawito Pawito; Ign. Agung Satyawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Consumers often purchase new products associated with preferred brand names. Their favorable attitude toward a brand name is often the result of repeated satisfaction with other products produced by the same company. Sometimes attitudes follow the purchase and consumption of a product. For example, consumers may purchase a branded product without having any prior attitude towards it because it is the only product of its kind available. There are many aspects to consumer behavior. The experience of using products and services, as well as the sense of pleasure derived from owning, collecting, or consuming goods and experiences contribute to consumer satisfaction and overall quality of life. These consumption outcomes or experiences, in turn, influence the consumer's future decision-making process. The importance of ownership and experience, a broader consumer behavior perspective may view consumer choice as the beginning of the consumption process, not just the end of the consumer's decision-making efforts.